Comparative evaluation of the impact on endothelial cells induced by different nanoparticle structures and functionalization - Landgraf, Lisa; Müller, Ines; Ernst, Peter; Schäfer, Miriam; Rosman, Christina; Schick, Isabel; Köhler, Oskar; Oehring, Hartmut; Breus, Vladimir V.; Basché, Thomas; Sönnichsen, Carsten; Tremel, Wolfgang; et al. (Beilstein Journal of Nanotechnology, 2015)
In the research field of nanoparticles, many studies demonstrated a high impact of the shape, size and surface charge, which is determined by the functionalization, of nanoparticles on cell viability and internalization into cells. This work focused on the comparison of three different nanoparticle types to give a better insight into general rules determining the biocompatibility of gold, Janus and semiconductor (quantum dot) nanoparticles. Endothelial cells were subject of this study, since blood is the first barrier after intravenous nanoparticle application. In particular, stronger effects on the viability of endothelial cells were found for nanoparticles with an elongated shape in comparison to spherical ones. Furthermore, a positively charged nanoparticle surface (NH2, CyA) leads to the strongest reduction in cell viability, whereas neutral and negatively charged nanoparticles are highly biocompatible to endothelial cells. These findings are attributed to a rapid internalization of the NH2-functionalized nanoparticles in combination with the damage of intracellular membranes. Interestingly, the endocytotic pathway seems to be a size-dependent process whereas nanoparticles with a size of 20 nm are internalized by caveolae-mediated endocytosis and nanoparticles with a size of 40 nm are taken up by clathrin-mediated internalization and macropinocytosis. Our results can be summarized to formulate five general rules, which are further specified in the text and which determine the biocompatibility of nanoparticles on endothelial cells. Our findings will help to design new nanoparticles with optimized properties concerning biocompatibility and uptake behavior with respect to the respective intended application.
Keywords: cell viability; gold nanoparticles; internalization; Janus particles; quantum dots